Pathways in Decentralised Collective Bargaining in Europe - Tros, Frank (Amsterdam University Press, 2023)
One of the main challenges in labour relations in Europe is the ongoing decentralisation of collective bargaining from national and sectoral levels to company levels. Decentralisation might be an answer to business needs in competitiveness and organisational flexibility. However, it risks erosion of collective bargaining structures, more inequality in employment conditions and fragmentation in trade unions' powers. Based on recent qualitative research, this book shows high varieties across European countries and economic sectors in degrees, forms and impacts of decentralisation. The authors explore, in interdisciplinary and multi-level perspectives, continuity and change in regulating and practicing collective bargaining in France, Germany, Ireland, Italy, the Netherlands, Poland, Spain and Sweden. In cross-country comparisons, company case studies in manufacturing and retail show the divergent effects of national regimes and social partners' power resources on trade unions' strategies and influence in company bargaining.